Intracranially injectable multi-siRNA nanomedicine for the inhibition of glioma stem cells. Issue 1 (18th August 2021) - Manju, Cheripelil Abraham; Jeena, Kottarapat; Ramachandran, Ranjith; Manohar, Maneesh; Ambily, Anna Mathew; Sajesh, Koythatta Meethalveedu; Gowd, Genekehal Siddaramana; Menon, Krishnakumar; Pavithran, Keechilat; Pillai, Ashok; Nair, Shantikumar V; Koyakutty, Manzoor
Abstract: Background: Nanoparticle siRNA-conjugates are promising clinical therapeutics as indicated by recent US-FDA approval. In glioma stem cells (GSC), multiple stemness associated genes were found aberrant. We report intracranially injectable, multi-gene-targeted siRNA nanoparticle gel (NPG) for the combinatorial silencing of 3 aberrant genes, thus inhibiting the tumorogenic potential of GSCs. Methods: NPG loaded with siRNAs targeted against FAK, NOTCH-1, and SOX-2 were prepared by the self-assembly of siRNAs with protamine–hyaluronic acid combination. Electron microscopy, DLS, and agarose gel electrophoresis were used for the physicochemical characterization. Cell transfection and gene-silencing efficiency were studied using human mesenchymal stem cells and rat C6 glioma-derived GSCs. Neurosphere inhibition was tested in vitro using GSCs derived from C6 cell line and glioma patient samples. Patient-derived xenograft model and orthotopic rat glioma model were used to test the effect of NPG on in vivo tumorigenicity. Results: The siRNA nanoparticles with an average size 250 nm and 95% loading efficiency showed cellular uptake in 95.5% GSCs. Simultaneous gene silencing of FAK, NOTCH-1, and SOX-2 led to the inhibition of neurosphere formation by GSCs, whereas normal stem cells remained unaffected and retained neuronal differentiation capability. GBM PDX models manifested significant impairment in the tumorigenic potential of NPG treated GSCs. Intracranial injection of NPG inhibited tumor growth in orthotopic rat brain tumor model. Conclusion: Intracranially injectable n-siRNA NPG targeted to multiple stem-cell signaling impairs glioma initiation capabilities of GSCs and inhibited tumor growth in vivo.